Profile of a group of university audience in Mexico according to their citizen participation, trust in institutions and civic interaction in the media in 2017 - Gutiérrez-Rentería, María-Elena (2019)
The present quantitative study shows the singularities of the university audience in Mexico in 2017, measured according to their civic participation, how they assess national institutions, and how they interact with the media regarding social and political issues. The surveyed population consisted of 1,195 young adults of 23 years of average age and who are part of private universities located in Jalisco, Mexico City and Aguascalientes. The results indicate that the offline participation in social capital is more significant than online participation of this university audience. The only institutions that have an approval index for this audience are religious institutions, universities, and the media. Finally, the university audience in Mexico has features of being passive and conservative regarding its consumption of information and its political participation in media. This population reflects apathy in expressing their opinion in media regarding social and political issues in the country.